Effect of allogenic bone transplantation from the iliac crest and mandible on fracture healing in rat tibia - Karabulut, Burak; Tanrisever, Murat; Guney, Merve; Dogan, Delil; Donmezer, Tugce; Istek, Ozmen; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2026)
The aim of this study was to compare the healing performance of non-vascularized bone allografts harvested from the mandible and the iliac crest in an experimental rat tibial fracture model. The rats selected as subjects were divided into four groups: the jaw allogeneic bone (n = 7), the iliac allogeneic bone (n = 7), the fracture control group (n = 7), and the donor group (n = 4). The donor rats were first sacrificed, and 5 mm thick and 5 mm wide block grafts were obtained from the corticocancellous bone portion of the mandible and iliac bones, both right and left. These grafts were securely fixed with Kirshner wires between two bone fragments obtained by cutting the corticocancellous bone portion of the rats' right tibias with a disc under serum irrigation. In the control fracture group, a fracture was created only in the tibia and securely fixed with Kirshner wires. After an eight week healing period, all rats were sacrificed, and their bone tissues were collected for analysis. Healing at the fracture line was assessed by the percentage of new bone formation for each sample. Data were analyzed using the Kruskal Wallis and Mann Whitney U tests. The percentage of new bone formation in the mandibular allogeneic transplantation group was higher than in the control and iliac crest groups (P < 0,05). New bone formation in the iliac crest allotransplantation group was lower than in the control group (P < 0,05). Non-vascularized allografts of mandibular origin showed higher new bone formation in the experimental rat tibial fracture model. These findings suggest that the donor site may play a significant role in determining the biological behavior and regenerative capacity of bone allografts.
Efecto del trasplante óseo alogénico de la cresta ilíaca y la mandíbula sobre la consolidación de fracturas en tibia de rata
Keywords: Allograft transplantation; non-vascular allograft; new bone formation; tibia fracture; rat